Wirtschaftswachstum hat in Ost-Mitteleuropa Höhepunkt vorläufig überschritten; Central and East European Economies Moderate Slowdown - Josef Pöschl (The Vienna Institute for International Economic Studies (wiiw), 2001)
Die Hoffnung, dass im Jahr 2000 die Wirtschaft erstmals in allen ostmitteleuropäischen Ländern (MOEL) wachsen würde, hat sich erfüllt. Die schwierigste Phase des Umbaus scheint nunmehr überall überwunden zu sein. Die Anfälligkeit für Rückschläge bleibt bestehen, aber je nach der wirtschaftlichen Reife der einzelnen Länder in sehr unterschiedlichem Maße. Die sich abzeichnende Abschwächung der Weltkonjunktur wird voraussichtlich auch Ost-Mitteleuropa erfassen. – – After the Boom in 2000 In the year 2000, for the first time since the beginning of transformation the economy grew in all Central and East European countries (CEECs). All countries managed to accommodate the shock of high oil prices - no currency, current account, or banking crisis occurred. Croatia, the Czech Republic, Romania and Ukraine pulled themselves out of recession, and so did the Federal Republic of Yugoslavia, under very special conditions. The CEECs gained from the business climate in the European Union and in the USA, but this positive influence will lose strength in 2001. The picture in this year will be mixed. Some countries will continue to recover further from recession or near-stagnation, others, such as Poland and Russia, both important due their size, are likely to achieve less growth than last year. Poland is plagued by a high current account deficit and a stagnating domestic demand, Russia is confronted with less favourable world market prices for oil and a gradual real appreciation of the currency. Over the whole region, growth will continue in 2002, but disturbances are always possible, as the countries are vulnerable to external influences, and some of them are still struggling with irregularities in their financial system.
Additional information: Reprint from: WIFO-Monatsberichte, Vol. 74, No. 5, May 2001
Keywords: 330